Treatment of neovaginal prolapse: case report and systematic review of the literature. (January 2017) - Neron, Mathias; Ferron, Gwenaël; Vieille, Pierre; Letouzey, Vincent; Fatton, Brigitte; Tayrac, Renaud
Abstract Introduction and Hypothesis Neovaginal prolapse (NP) is a rare event as few cases have been reported in the literature. Its management is complex and depends on the initial pathology, the vaginoplasty technique and the patient's history. We present a review the literature on this rare event. Methods We describe the case of a 72-year-old woman who presented with NP 1 year after pelvic exenteration and radiotherapy for recurrent cervical carcinoma associated with vaginal reconstruction by shaped-tube omentoplasty. She had undergone two previous surgical procedures (posterior sacrospinous ligament suspension and partial colpocleisis), but NP recurred each time within a few months. We performed an anterior approach to the sacrospinous ligament and inserted a mesh under the anterior wall of the neovagina, with the two mesh arms driven through the sacrospinous ligament in a tension-free manner (Uphold Lite® system). The MEDLINE, Cochrane Library, ClinicalTrials and OpenGrey databases were systematically searched for literature on the management of NP following bowel vaginoplasty, mechanical dilatation, graciloplasty, omentoplasty, rectus abdominis myocutaneous flap and the Davydov procedure. Results The postoperative course in the patient whose case is described was uneventful and after 1 year of follow-up, the anatomical results and patient satisfaction were good. The systematic search of the databases revealed several studies on the treatment of NP using abdominal and vaginal approaches, and these are reviewed. Conclusions Overall, sacrocolpopexy would appear to be a good option for the treatment of prolapse after bowel vaginoplasty, but too few cases have been reported to establish this technique as the standard management of NP.